2006
DOI: 10.1016/j.cardiores.2005.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effect of p38 MAP kinase and JNK inhibitors on the development of heart failure in the cardiomyopathic hamster

Abstract: These results suggest that chronic treatment with p38 MAPK and JNK inhibitors produces opposing effects on the development of heart failure in the DCM hamster heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 30 publications
5
50
0
5
Order By: Relevance
“…In the infarct heart, cytokines such as tumor necrosis factor and interleukin 6 and injury of ischemia‐reperfusion activate the p38 signaling pathway 26. Furthermore, as a critical part of the response to MI in the heart, several investigations have confirmed that the p38 pathway sensitizes the caspase cascade to induce cell apoptosis, which supports our findings 27, 28. We observed that the activation of p38 was attenuated by knockdown of TGFβR3 under H 2 O 2 or MI conditions.…”
Section: Discussionsupporting
confidence: 88%
“…In the infarct heart, cytokines such as tumor necrosis factor and interleukin 6 and injury of ischemia‐reperfusion activate the p38 signaling pathway 26. Furthermore, as a critical part of the response to MI in the heart, several investigations have confirmed that the p38 pathway sensitizes the caspase cascade to induce cell apoptosis, which supports our findings 27, 28. We observed that the activation of p38 was attenuated by knockdown of TGFβR3 under H 2 O 2 or MI conditions.…”
Section: Discussionsupporting
confidence: 88%
“…Deletion of JNK1 in the heart exacerbates fibrosis upon pressure overload (27). Chronic treatment with a JNK inhibitor, SP600125, increases apoptosis in cardiomyocytes and interstitial fibrosis in a hamster model of cardiomyopathy (28). In line with these findings, the suppression of JNK by miR-433 or siRNA was shown to trigger CF in the present study.…”
supporting
confidence: 84%
“…Thus pharmacologic inhibition of JNK or p38 as a treatment for human heart disease would be more complicated if these animal studies directly translate (Figure 2). However, hamsters with muscular dystrophy and associated heart disease show less fibrosis and better cardiac function with systemic p38 MAPK inhibitor treatment, though a JNK inhibitor has no effect (114). Similar cardioprotection has also been observed in diabetic mice treated with a p38 MAPK inhibitor (115) and in mice following myocardial infarction injury (116).…”
Section: Mapk Inhibitionmentioning
confidence: 76%